2004
DOI: 10.1029/2004ja010709
|View full text |Cite
|
Sign up to set email alerts
|

Midlatitude ionospheric plasma temperature climatology and empirical model based on Saint Santin incoherent scatter radar data from 1966 to 1987

Abstract: [1] Ionospheric plasma temperature variations have recently been studied based on incoherent scatter radar (ISR) observations at a lower midlatitude site, Shigaraki, in East Asia ] and Millstone Hill, a typical subauroral midlatitude site in North America [Zhang and Holt, 2004]. The French Saint Santin ISR, with a geographic latitude slightly higher but an apex latitude 14°lower than Millstone, collected bistatic and quadristatic measurements for over two solar cycles beginning in September 1965. A database of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 30 publications
6
50
0
1
Order By: Relevance
“…That is, at higher altitudes (above ∼300 km), the photoelectron heat not only comes from local hemisphere but also from the conjugate hemisphere. Some studies have shown presunrise plasma temperature enhancements was contributed to by the photoelectron heating from the conjugate sunlit region (Evans, 1973;Peterson et al, 1977;Chao et al, 2003, Zhang et al, 2004. During a solar eclipse, photoelectrons in the eclipse region are reduced largely at totality, then in its conjugate region the inflow photoelectron flux from the eclipse region will decrease a lot, which results in a large decrease in electron temperature in this region.…”
Section: Discussionmentioning
confidence: 99%
“…That is, at higher altitudes (above ∼300 km), the photoelectron heat not only comes from local hemisphere but also from the conjugate hemisphere. Some studies have shown presunrise plasma temperature enhancements was contributed to by the photoelectron heating from the conjugate sunlit region (Evans, 1973;Peterson et al, 1977;Chao et al, 2003, Zhang et al, 2004. During a solar eclipse, photoelectrons in the eclipse region are reduced largely at totality, then in its conjugate region the inflow photoelectron flux from the eclipse region will decrease a lot, which results in a large decrease in electron temperature in this region.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of the energetic photoelectron flow from a conjugate sunlit hemisphere to a darkness hemisphere has been mentioned and considered in some papers in the past (e.g. Evans, 1973;Schunk and Nagy, 1978;Bailey and Sellek, 1990;Chao et al, 2003, Zhang et al, 2004Lei et al, 2007;Bilitza et al, 2007). When the Northern Hemisphere is in darkness during the eclipse, the magnetic conjugate-points in the Southern Hemisphere are still illuminated.…”
Section: Ionospheric Disturbances In the Conjugate Hemispherementioning
confidence: 99%
“…As a result photoionization activity in the ionosphere during the eclipse period decreases to almost nighttime conditions. The changes in the electron density distribution and the total electron content (TEC) have been studied using different techniques such as the Faraday rotation measurements (Tyagi et al, 1980;DasGupta et al, 1981), ionosonde networks (Venkatesh et al, 2011), incoherent scatter radars (Zhang et al, 2004), GPS systems (Ramarao et al, 2006) and satellite measurements (Davies and Hartmann, 1997). GPS systems provide data with better accuracy both in time and space and hence are widely used in ground-based studies (Bagiya et al, 2011;Kumar and Singh, 2011;Galav et al, 2011).…”
Section: Introductionmentioning
confidence: 99%